Barriers to treatment adherence of patients with low back pain in physiotherapy outpatient clinics in the kingdom of Eswatini - Chikaka, Tapiwa Lorraine (My University, 2022)
Background: Adherence to a management regime is a key to any successful treatment plan resulting in a positive health and socioeconomic outcome. Barriers to the adherence of treatment plans do exist. These barriers contribute to a negative outcome on the health and socioeconomic status of an individual. Physiotherapy management of low back pain is not immune to these barriers. Barriers to physiotherapy treatment of low back pain in the Kingdom of Eswatini are unknown. This study was done to establish these barriers to treatment adherence of physiotherapy low back pain management. Study Aim: To determine barriers associated with physiotherapy treatment adherence among patients with low back pain in outpatient physiotherapy clinics in the Kingdom of Eswatini. Methodology: This study was a crossectional descriptive survey using a self-developed REDCap survey to collect data. A pilot study was first conducted before the main study. The study sample consisted of 62 participants with low back pain. A descriptive analysis, regression analysis and bivariate analysis with odds ratios was used to determine the barriers to physiotherapy treatment adherence. Results: Forty (64.5%) of the participants reported that they did not miss their scheduled physiotherapy appointments. The main barriers highlighted were because, they already feel better (59.7%), they have other important priorities (42.9%), their schedules are already full (57.1%), they are too busy (57.1%), they rarely have an opportunity in their day (42.9%), they are only available during the weekends or night time (28.6%) and the physiotherapy clinic was too far (7.1%). Adherence was significantly associated with understanding of the condition (p= 0.001) and too many exercises (p= 0.05). The older the patient was less associated with less chances of defaulting. Females are less likely to default than males and patients are three times more likely to attend sessions if reffered by a doctor as compared to anyone else. Conclusion: Although the participating patients identified different barriers for nonattendance, these barriers still pose a potential to cause non-adherence. There is a need to assess barriers in every patient population to understand their different challenges and deliver patient-centred care. Some barriers highlighted were due to the occurrences of the Covid-19 pandemic and the country political unrest. It is during these times that therapists should strategize to give proper care to the patients.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science in Physiotherapy Orthopaedic Surgery to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, 2022